Manufacturing of polymer-based 1×2 Y-branch symmetric and asymmetric waveguide coupler through moulding technique - M. S. M., Ghazali; F. R. M., Romlay; A. A., Ehsan (Universiti Malaysia Pahang, 2021)
Manufacturing of Y-branch coupler depends on high technology production equipment and in-factory accuracy assembly tools. The manufacturing of a 1×2 Y-branch symmetric and asymmetric waveguide coupler based on the mould replication process and Epoxy OG142 as an optical core is presented; an alternative to provide a less complex technique. The polymer optical waveguide adopted two basic designs: the 1×2 Y-branch symmetric coupler as the core structure and the 1×2 asymmetric coupler that allows non-symmetric optical splitting. This paper focused on the main structure fabrication of the 1×2 symmetric and asymmetric waveguide coupler that produces a power output. The fabrication was done by engraving acrylic to produce a master mould using CNC machining tools for optical devices. Both 1×2 devices were made via soft lithography, which duplicated the pattern from the master mould onto a second mould to produce an actual device. Optical polymer epoxy OG142 was injected into the second mould, of which the product was then put on top of acrylic. The device was completed after curing the optical polymer glue, epoxy OG142, by exposing the assembly on the second mould under UV light until both parts bonded. The difference between the simulation and design TOFR value was only ±2%. This showed that the simulation and design are in good agreement, which provides similar performance.